2022
DOI: 10.1093/toxres/tfac018
|View full text |Cite
|
Sign up to set email alerts
|

Sacubitril/valsartan protects against arsenic trioxide induced cardiotoxicity in vivo and in vitro

Abstract: The cardiotoxicity induced by arsenic trioxide (ATO) limits its clinical application in acute promyelocytic leukemia treatment. Sacubitril/valsartan (LCZ696) is an effective drug for the treatment of heart failure. In this study, we aimed to investigate the protective effect and mechanisms of LCZ696 against the ATO-induced cardiotoxicity in mice and H9c2 cells. We found that LCZ696 could alleviate the decrease of ejection fraction and fractional shortening induced by ATO, thereby improving mouse cardiac contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…It might be secondary to increased oxidative stress and intracellular calcium overload. Several ongoing studies are investigating the potential of antioxidant and anti-inflammatory agents such as sacubitril/valsartan, resveratrol, L-ascorbic acid, and omega-3 fatty acids as potential therapeutic options to attenuate arsenic-induced cardiotoxicity [ 25 , 27 , 28 , 29 ]. Further research is needed to fully investigate and validate the efficacy of these treatments.…”
Section: Qt Prolongationmentioning
confidence: 99%
“…It might be secondary to increased oxidative stress and intracellular calcium overload. Several ongoing studies are investigating the potential of antioxidant and anti-inflammatory agents such as sacubitril/valsartan, resveratrol, L-ascorbic acid, and omega-3 fatty acids as potential therapeutic options to attenuate arsenic-induced cardiotoxicity [ 25 , 27 , 28 , 29 ]. Further research is needed to fully investigate and validate the efficacy of these treatments.…”
Section: Qt Prolongationmentioning
confidence: 99%
“…Protease inhibitor [37][38][39] Bortezomil/carfezomil CHF/myocardial ischemia/hypertension 1.8-7.2 Endocrinotherapy [40] Goserin/levoprorelin/flutamide/bicalutamide Myocardial infarction/CHF 0.1-5 CART cell therapy [41,42] Tisagenlecleucel/axicabtagene ciloleucel Tachycardia/hypotension/cardiac insufficiency Unclear Arsenic trioxide [43,44] Arsenic trioxide/all-trans retinoic acid Prolonged QT interval/tachycardia 16 Hematopoietic stem cell transplantation [45] Lenalidomide, bortezomib, Isazzomib Arrhythmia/myocardial ischemia/CHF 2-12…”
Section: -34mentioning
confidence: 99%
“…Patients who began taking sacubitril/valsartan in hospital had a lower risk profile for heart failure rehospitalization and cardiovascular death than patients with a delayed initiation of sacubitril/valsartan (8 weeks later) [39] . The clinical trials of sacubitril/valsartan in HFrEF were shown in Table 2 [37][38][39][40][41][42][43][44][45][46][47][48] . LV remodeling was crucial in progression to HFrEF [70] .…”
Section: Sacubitril/valsartan In Heart Failure Reduced Ejection Fractionmentioning
confidence: 99%